Cryogenic synthesis of nanodimensional magetite - Gorbyk, P.P.; Dubrovin, I.V.; Filonenko, M.M. (Functional Materials, 2007)
Low temperature synthesis of single-domain magnetite particles at the liquid-solid interface was developed. Spherical particles of crystalline magnetite with size of 6-50 nm were prepared. Investigation of phase and element composition as well as morphology of single-domain magnetite was performed with the help of X-ray phase analysis, Auger-spectroscopy, raster electronic and atomic force microscopy.